2010
DOI: 10.1097/brs.0b013e3181c62294
|View full text |Cite
|
Sign up to set email alerts
|

Life Quality After Instrumented Lumbar Fusion in the Elderly

Abstract: Age itself cannot be considered a contraindication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…Although in the literature there are no conclusive studies conducted on elderly patients, good clinical results are described with improvements both in VAS and ODI of 45 and 27 %, respectively [2,3,6,15,16]. Our results are inline with published data, with a significant score improvement both on VAS and ODI, at the latest check.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although in the literature there are no conclusive studies conducted on elderly patients, good clinical results are described with improvements both in VAS and ODI of 45 and 27 %, respectively [2,3,6,15,16]. Our results are inline with published data, with a significant score improvement both on VAS and ODI, at the latest check.…”
Section: Discussionsupporting
confidence: 87%
“…The radiological exams showed initial signs of fusion in 52 cases: in one case bony reabsorption around screws of L5 were detected and the patient underwent revision surgery of the instrumentation. The last follow-up performed at 18.4 months (range [15][16][17][18][19][20] was completed for 49 patients of the initial 53: one had died and the other three were lost at the follow-up time. The mean final clinical evaluation tools were: VAS = 1.8 and ODI = 21.8 %, with a statistically significant improvement (p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…This supports previously published data by Becker et al, 1 who demonstrated an improvement in QOL measures in elderly patients following instrumented lumbar fusion. These data bolster the case for not considering age to be an inherent contraindication to instrumented fusion.…”
supporting
confidence: 82%
“…They were able to demonstrate that e elderly patients benefit from spinal fusion but they do not distinguish between the two methods [13]. …”
Section: Discussionmentioning
confidence: 99%